Covid-19, China and the future of global development - Seth Schindler; Nicholas Jepson; Wenxing Cui (Research in Globalization, 2020)
Tensions between the United States and China have been escalating in recent years, and the Covid-19 pandemic has intensified their competition. If sustained, China's more effective public health response and economic restart will burnish its leadership credentials in the field of global development. This article lays out the origins and distinctive features of China's development policies and vision, and argues that in a post-Covid world these may constitute an appealing alternative to the US-led development paradigm for many developing countries. We contrast the universalism and rigidity of contemporary development orthodoxy with China's emphasis on bilateral and pragmatic forms of development cooperation borne out of its domestic experience. While Chinese development assistance and loans enhance its soft power, partner countries are offered significant autonomy and flexibility. We conclude by outlining three factors which may impact the future of Chinese leadership in the field of global development; a reconciliation of global financial governance and China's development lending, the outcome of the upcoming American presidential election and domestic discontent within China over the Belt and Road Initiative.
Keywords: 330; Belt and road initiative; China; Covid-19; Global development; United States